Reconstruction of the proto-type basin and tectono-paleographical evolution of Tarim in the Cenozoic - Wei, Lunyan; Huang, Shaoying; Luo, Caiming; Duan, Yunjiang; Xia, Jinkai; Zhong, Ziqi; Li, Xiang; Chang, Haining (Frontiers in Earth Science, 2023)
Reconstruction of proto-type basin and tectono-paleogeography is helpful to understand the different stages of evolution of the sedimentary basin and basin-mountain relationship. It is nonnegligible and significant to combine the basin with regional tectonic background for discussing the process of basin-mountain coupling and the tectonic evolution of the peripheral orogenic belts. With reliable residual thickness map and lithofacies map of the Tarim Basin in Cenozoic, based on our quantified shortening amount of previous works and 81 balanced cross-sections, we restore the original range and compile the proto-type basin map of Tarim Basin. From a compilation of previous studies on the lithofacies of peripheral blocks, reconstruct tectono-paleogeography of the Tarim Basin in Cenozoic. The Indian plate collided with the Eurasian continent at ~45-40 Ma. The remote effect of the collision led to the resurrection and reactivation of the Kunlun and Tianshan Mountains. The Southwest Tarim and Kuqa rejuvenated foreland basins separately developed along the north front of Kunlun mountain and the south front of Tianshan mountain. The tectonic evolution process of the Tarim Basin in Cenozoic is divided into two stages: (1) In Paleogene, the Neo-Tethys Ocean retreated stepwise westward from the Southwest of the Tarim Basin, and the sedimentary lithofacies of the Southwest Tarim Depression were bay lagoon facies and lake facies. (2) As the Neo-Tethys Ocean sea retreat finally occurred at the Tarim Basin during Late Oligocene - Early Miocene, it became an almost closed terrestrial basin, in the sediment with the deposition of fluvial facies and lacustrine facies. The Cenozoic tectono-paleogeography of Tarim Basin is closely related to the close of Neo-Tethys ocean and the reactivation of the Kunlun and Tianshan Mountains.